Edificio Novartis (2003)
Edificio de oficinas en Buenos Aires.
Keywords: ARGENTINA; BUENOS AIRES; EDIFICIOS DE OFICINAS; ARQUITECTURA CORPORATIVA; ASLAN Y EZCURRA Y ASOCIADOS ARQUITECTOS; ASLAN, JOSÉ; EZCURRA, HECTOR